Effect of inter-pregnancy interval on pregnancy outcome - Sumayya, Tabassum; Meghana, Kanchibhotla; Gonnabaktula, Naga Vasantha Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The inter-pregnancy interval (IPI) significantly impacts maternal and child health outcomes. Objective of the study was to determine the effect of inter-pregnancy interval on maternal and foetal outcome. Methods: This prospective observational study was conducted at Sri Ramachandra Institute of Higher Education and Research Institute from September 2022 to April 2024. A total of 385 pregnant women in their second pregnancy were categorized into three groups based on the inter-pregnancy interval as short (<24 months), optimal (24-59 months), and long (>59 months). Data on maternal outcomes, intrapartum assessments, and foetal complications were collected and analysed using descriptive and comparative statistics. Results: Out of 385 participants, 37.1% had an IPI of <24 months, 55.1% had an IPI of 24-59 months, and 7.8% had an IPI of >59 months. Shorter IPIs were associated with higher rates of anaemia (77%) and postpartum haemorrhage (45.8%). Longer IPIs were linked to increased gestational diabetes (50%) and hypertensive disorders (63.3%). Foetal complications such as macrosomia were more common in the longer IPIs group (16%). Conclusions: Both short and long IPIs are linked with adverse maternal and foetal outcomes, emphasizing the need for optimal spacing between pregnancies to improve health outcomes.